Serotonin shapes the migratory potential of NK cells - Zimmer, Philipp (International journal of sports medicine, 2017)
Increased serotonin (5-HT) levels have been shown to influence natural killer cell (NK cell) function. Acute exercise mobilizes and activates NK cells and further increases serum 5-HT concentrations in a dose-dependent manner. The aim of this study was to investigate the impact of different serum 5-HT concentrations on NK cell migratory potential and cytotoxicity. The human NK cell line KHYG-1 was assigned to 4 conditions, including 3 physiological concentrations of 5-HT (100, 130 or 170 µg/l 5-HT) and one control condition. NK cells were analyzed regarding cytotoxicity, migratory potential and expression of adhesion molecules. No treatment effect on NK cell cytotoxicity and expression of integrin subunits was detected. Migratory potential was increased in a dose dependent manner, indicating the highest protease activity in cells that were incubated with 170 µg/l 5-HT (170 µg/l vs. control, p<0.001, 170 µg/l vs. 100 µg/l, p<0.001; 170 µg/l vs. 130 µg/l, p=0.003; 130 µg/l vs. control, p<0.001, 130 µg/l vs. 100 µg/l, p<0.001). These results suggest that elevated 5-HT serum levels play a mediating role in NK cell function. As exercise has been shown to be involved in NK cell mobilization and redistribution, the influence of 5-HT should be investigated in ex vivo and in vivo experiments.
Gesehen am 20.08.2018